2009
DOI: 10.2174/1567209197471562050
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Concentration and Cognitive Impairment

Abstract: Results from clinical samples suggest low serum albumin may be associated with cognitive impairment, though evidence from population-based studies is inconclusive. Participants were 1,752 adults (699 men and 1,053 women) aged 65 years and over from the Health Survey for England 2000, a nationally representative population-based study. Cognitive impairment was assessed using the Abbreviated Mental Test Score. The cross-sectional relation of serum albumin quartiles to cognitive impairment was modelled using logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…Regarding nutrition, many reports have shown that hypoalbuminemia is associated with cognitive dysfunction . From the preventive perspective, albumin has been reported to have an anti‐oxidant effect, mitigating toxicity and inhibiting the formation of amyloid β peptide fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding nutrition, many reports have shown that hypoalbuminemia is associated with cognitive dysfunction . From the preventive perspective, albumin has been reported to have an anti‐oxidant effect, mitigating toxicity and inhibiting the formation of amyloid β peptide fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that plasma protein dysfunctions affect the clearance of Ab from the CNS and consequently Ab plaque deposition within the brain. For instance, recent clinical studies show that low albumin levels are associated with increased odds of cognitive impairment and, moreover, indicate the use of albumin in plasma exchange therapies as a promising avenue in the treatment of mild to moderate Alzheimer's disease (2,3). Furthermore, HSA is also an effective inhibitor of Ab fibrilization (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of A␤ self-association by HSA has both pathological implications and therapeutic potential (4 -7). Low serum albumin concentrations have been reported to be associated with increased cognitive impairment in elderly patients (4), and plasmapheresis with therapeutic albumin is currently being assessed in clinical trials as a potential treatment for mild to moderate Alzheimer's disease (8,9). The pathological and therapeutic potential of HSA warrants a comprehensive understanding of the molecular mechanism underlying the HSA-A␤ interactions, not only to improve the HSA therapeutic efficiency but also to elucidate basic principles of amyloid inhibition that will facilitate the design of new amyloid inhibitors (10 -17).…”
mentioning
confidence: 99%